Re-wiring Guilt: How Advancing Neuroscience Encourages Strategic Interventions Over Retributive Justice - Anderson, Nathaniel E.; Kiehl, Kent A. (Frontiers in Psychology, 2020)
The increasing visibility of neuroscience employed in legal contexts has rightfully prompted critical discourse regarding the boundaries of its utility. High profile debates include some extreme positions that either undermine the relevance of neuroscience or overstate its role in determining legal responsibility. Here we adopt a conciliatory attitude, reaffirming the current value of neuroscience in jurisprudence and addressing its role in shifting normative attitudes about culpability. Adopting a balanced perspective about the interaction between two dynamic fields (science and law) allows for more fruitful consideration of practical changes likely to improve the way we engage in legal decision-making. Neuroscience provides a useful platform for addressing nuanced and multifaceted deterministic factors promoting antisocial behavior. Ultimately, we suggest that shifting normative attitudes about culpability vis-à-vis advancing neuroscience are not likely to promote major changes in the way we assign legal responsibility. Rather, it helps us to shed our harshest retributivist instincts in favor of more pragmatic strategies for combating the most conspicuous patterns promoting mass incarceration and recidivism.